Improving Profitability Through Standard Profit Formulation, A Case Study Of Indonesian Small Contractor Service Company - Taufiqurrochman Taufiqurrochman; Ruslan Prijadi; Rambat Lupiyoadi (Syntax Literate, 2022)
This paper is based on quantitative research with a case study at a small-scale contractor service company engaged in civil, mechanical and electrical work in Indonesia. The owner, who also served as a director of the company, stated that his company faced a stagnant condition in the last three years, even though projects from customers were always there, internal audit found that there were problems with internal factors in the company, such as invalid financial reports, lack of working capital and unserved potential orders. The problem stems from a lack of competent resources in the administrative and finance sections. Because the owner serves as the finance and administration staff at the same time in order to save money on the company's expenses, decisions, financial records, and administration are not carried out properly, and the company does not know whether the project undertaken by the company makes a profit.This double hat role also raises another serious problem for the company, since the director neglects aspects of business development, due to leadership time being mostly spent on things that can be resolved at lower levels. In this study, a vicious circle pattern was discovered, which causes financial problems for the company despite the fact that it is working on many projects. Improvements in the organizational structure and the determination of profit standards are made so that the company can escape the vicious circle and finally be able to improve its profitability.